(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
During the 2011 excavation in Nora a handle fragment of an amphora with a stamp on the back was found. On it, the three letters “T. V. P.” are imprinted on the back, separated from two little triangles acting as partition points. This stamp is relevant to a Gauloise 4 amphora, produced in Narbonese Gaul and diffused between the 1st century and the 3rd century AD. It is one of the little evidence of trade relations between Gaul and southern Sardinia found in Nora.